ANALISIS KESALAHAN PENGGUNAAN KATA DALAM MENULIS PARAGRAF ARGUMENTASI OLEH SISWA - Denita Giawa (Universitas Nias Raya, 2024)
The background to the problem in this research is that there are still errors in choosing words or diction such as denotation, connotation, synonyms, general words and special words in writing argumentative paragraphs. These errors can cause readers to misinterpret the meaning of the argumentation paragraph written by the student. This research aims to describe errors in denotation, connotation, synonyms, general words and special words. The approach used in this research is a descriptive approach. This research data was analyzed in three stages, namely data reduction, verification and conclusion drawing. The results of this research were from eighteen seventh grade students, six argumentative paragraph texts which had denotation word errors, one argumentative paragraph text which had connotation word errors, three argumentative paragraph texts which had synonym word errors, two argumentative paragraph texts which had word errors. In general, two argumentative paragraph texts that have specific word errors and those that do not have word errors are four argumentative paragraph texts. This word error occurs because students still don't know the more appropriate and better words to use in argumentative paragraphs. Suggestions for future researchers, the results of this research can be used as material for further research on word errors in writing argumentative paragraphs.